COUNSELING PROGRAM MANAGEMENT IN THE INDEPENDENT CURRICULUM AT MOVING SCHOOLS - Ramasepa, Nuzlita; Rizki, Sari; Zahriyanti, Zahriyanti (Jurnal As-Salam, 2025)
This research aims to analyze the planning, organization, implementation, and evaluation of the guidance and counseling program at the high school level in the Bireuen Regency. A qualitative research design using a case study approach was conducted at two high schools in Bireuen Regency: SMA Negeri 1 Kuala and SMA Negeri 1 Jeunieb. Data collection techniques included interviews, observation, and documentation, and the data were processed using analysis techniques to reduce, present, and verify the information. The findings indicate that the planning of the guidance and counseling program has been effectively carried out, with needs assessments conducted and transformed into an annual action plan aimed at enhancing the character profile of Pancasila students. The organization of the program has also been smooth, with school leadership ensuring the necessary resources and delegating the responsibility of counseling guidance to teachers, thus preparing for potential shortages of the dedicated counseling staff. Despite this, the implementation of the program is still ongoing, with gaps in service coverage. The program has four main components: basic services, specialization and individual planning services, responsive services, and system support, all designed to support students' optimal development and alignment with the Pancasila student profile. The evaluation of the program is still in progress but has not yet reached its full potential. Evaluation activities include setting performance standards, assessing outcomes, and implementing corrective actions. In conclusion, while the guidance and counseling program at the high school level in Bireuen Regency is progressing positively, further improvements are needed, particularly in expanding services and fully implementing evaluation measures. The implications of this research highlight the need for further professional development for counseling teachers, better resource allocation, and the expansion of the evaluation process to ensure the program's continued success and alignment with educational goals.